(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2023)
The sedimentological characteristics and fossil vertebrates studies are notoriously increasing in the earth sciences field, as a way to infer reliable information about the biota and the paleoenvironmental and paleoclimatic context. In this framework, we establish relationships among the flora, fauna and the depositional environment during the Late Miocene in Northwestern Argentina. The sedimentology features are described in detail from sediments collected in the Quebrada Salta section, and the Xenarthra Cingulata Kraglievichia paranensis (Pampatheriidae) and Cranithlastus xibiensis (Glyptodontidae) are recorded for the first time in the Palo Pintado Formation (Salta Province, Argentina). The sedimentary observations support the presence of a sinuous sandy-gravel fluvial system with swamps and lacustrine, under a wet tropical climate. In this environment, the vertebrates here described would have inhabited open zones close to these freshwater bodies, predominated by xeric vegetation, mainly represented by grasses and sedges with scarce arboreous elements.